2014
DOI: 10.1017/s1479262114000136
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-level and trait-level differentiation between the cultivated apple (Malus× domesticaBorkh.) and its main progenitorMalussieversii

Abstract: The present study is the first to compare the trait-level differentiation (Q st ) and the molecular-level differentiation (F st ) between Malus £ domestica and Malus sieversii. A set of 115 accessions representing M. £ domestica (99) and M. sieversii (16) were genotyped using the International RosBREED SNP Consortium apple 8K SNP array and phenotyped for eight fruit quality traits in a clonally replicated experiment. A set of 3521 single nucleotide polymorphisms (SNPs) with an average call rate of 98% was reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 55 publications
(108 reference statements)
3
27
0
Order By: Relevance
“…in the Genetic Resources Information Network (GRIN; U. S. Department of Agriculture, 2014) were designated as M. sieversii in our analyses, because of the high degree of similarity among the accessions associated with these two species names (Volk et al, 2013; Kumar et al, 2014). A Sorbus aucuparia L. individual (PI 635088) from the U. S. National Arboretum, Washington, D.C., was selected for use as an outgroup for phylogenetic and network analyses (Potter et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…in the Genetic Resources Information Network (GRIN; U. S. Department of Agriculture, 2014) were designated as M. sieversii in our analyses, because of the high degree of similarity among the accessions associated with these two species names (Volk et al, 2013; Kumar et al, 2014). A Sorbus aucuparia L. individual (PI 635088) from the U. S. National Arboretum, Washington, D.C., was selected for use as an outgroup for phylogenetic and network analyses (Potter et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…() in two core collections of unrelated accessions of dessert and cider apples, while Kumar et al . () reported an r ² below 0.13 within 100 kbp in a diverse population of apple accessions. Moreover, even the 20K apple Infinium ® array was based on a restricted number of accessions (13) in the discovery panel, and although this tool perfectly suits the needs of PBA investigations (Allard et al ., ), its application to GWA studies is limited by the restricted genetic background on which it is based (Gross et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…A number of studies have reported the use of the two medium-density Infinium â arrays for the generation of a number of saturated genetic linkage maps and QTL detection (Antanaviciute et al, 2012;Clark et al, 2014;Falginella et al, 2015) in bi-parental full-sib families, for pedigree-based analysis (PBA) on multiple pedigreed families (Guan et al, 2015;Allard et al, 2016) or for GWA analysis in a family-based design (Kumar et al, 2013). However, GWA studies using the 8K SNP array in collections of unre-lated apple accessions (Kumar et al, 2014;Leforestier et al, 2015) highlighted the limitations of the arrays available to date, which provide a low density of markers for GWA studies as LD decays quite quickly in apple. An r 2 below 0.2 within 100 kbp was in fact reported by Leforestier et al (2015) in two core collections of unrelated accessions of dessert and cider apples, while Kumar et al (2014) reported an r² below 0.13 within 100 kbp in a diverse population of apple accessions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In apple, different populations were recently researched about association between SNP array and various traits including firmness, texture, over‐colour (Di Guardo et al., ; Kumar, Raulier, Chagné, & Whitworth, ; Kumar et al., ). Thus, we object to select of analysis germplasm and confirm possibility of GBS‐GWAS in apple.…”
Section: Discussionmentioning
confidence: 99%